Women waging war and peace : international perspectives of women's roles in conflict and post-conflict reconstruction - Cheldelin, Sandra; Eliatamby, Maneshka (Continuum, 2011)
The essays examine how women actively contribute not only to conflict, but also to peace and social change in diverse contexts around the world.